Avaliação das queixas osteomusculares e dos níveis de percepção de estresse como subsídios para a implantação de programas de promoção de saúde no ambiente de trabalho do setor de produção da indústria calçadista - Almeida, Larissa Brentini de (2012)
Although there are studies that relate the psychosocial conditions with musculoskeletal disorders, this association is not yet completely clear, especially among workers in the shoe industry. In this sense, the objective of this study was to determine the prevalence of musculoskeletal complaints and the level of perceived stress among workers in the production sector of the footwear industry in Franca and region and identify possible associations between these variables. Participants were 357 employees of the production sector of the footwear industry in Franca-SP and region. Participants completed a questionnaire to collect sociodemographic and occupational Scale of Perceived Stress (EPS-10) and the Nordic Musculoskeletal Questionnaire. The mean age of the sample was 10.4 ± 33.8 years, 51% male and 49% female. Among the subjects, 66.1% reported musculoskeletal complaints in the last twelve months and 33.3% in the last seven days. We observed a higher prevalence of complaints (29,1%) in the regions of wrists / hands / fingers. Regarding the perception of stress, the mean score of the EPS-10 was 16.1 ± 6.6. This result was significantly associated with the prevalence of musculoskeletal complaints in the last twelve months (p = 0.0017) and in the last seven days (p = 0.0006). It was also significant association between levels of perceived stress and the number of musculoskeletal complaints in the past 12 months (p <0.0001), but not in the last seven days (p = 0.3279). The results of this study indicated a high prevalence of musculoskeletal symptoms among workers evaluated, especially in the upper extremities, and a significant association with levels of perceived stress, which demonstrates the need for prevention and health promotion in the workplace.